Legal Issues Transformation Certificate Electronic Based on Land Registration Policy Electronic Based - Novieyani Wiratmaja; Abdul Rokhim (Dinasti Research, 2025)
A land rights certificate is proof of ownership of land rights for the holder of the land rights in question. The impact resulting from current advances and technological developments can create new legal acts. Initially, electronic certificates were not in line with the considerations of the Ministerial Regulation because a policy emerged among the public which reaped many objections. This study aims to identify legal issues related to the electronic issuance of certificates based on the land registration policy, as stipulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 1 of 2021 on Electronic Certificates. This study employs normative legal research, relying on both primary and secondary legal sources. Data was gathered through a thorough review of relevant literature. The research utilizes a statutory approach, focusing on the analysis of legal regulations. The research results show that First data security and privacy side, second lack of legal certainty over land, and third Land problems are land disputes that still occur frequently. The policy of launching electronic certificates based on the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 1 of 2021 has the potential to cause legal problems in the land law enforcement process